2021
DOI: 10.3390/ijerph182111176
|View full text |Cite
|
Sign up to set email alerts
|

Population Adherence to Infection Control Behaviors during Hong Kong’s First and Third COVID-19 Waves: A Serial Cross-Sectional Study

Abstract: Background: Although COVID-19 has affected over 220 countries by October 2021, there is limited research examining the patterns and determinants of adherence to infection control measures over time. Aims: Our study examines the sociodemographic factors associated with changes in the frequency of adherence to personal hygiene and social distancing behaviors in Hong Kong. Methods: A serial cross-sectional telephone survey in the general population was conducted during the first (March 2020) (n = 765) and third w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…A follow-up cross-sectional study conducted after the city’s third wave of COVID-19 indicated an increase in population-wide fatigue for adhering to anti-pandemic behaviour and practices, although the belief in the importance of these measures with regard to disease protection did not vary [ 9 ]. Planning and policymaking over the course of a protract crisis will evolve, following real-time interval-based monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…A follow-up cross-sectional study conducted after the city’s third wave of COVID-19 indicated an increase in population-wide fatigue for adhering to anti-pandemic behaviour and practices, although the belief in the importance of these measures with regard to disease protection did not vary [ 9 ]. Planning and policymaking over the course of a protract crisis will evolve, following real-time interval-based monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…Chan et al (2021) use repeated cross-sectional data to examine the socio-economic and demographic correlates of changing adherence to social distancing and personal hygiene measures in Hong Kong during the first and third waves of COVID-19. They find improved adherence to mask wearing and decreasing compliance with social distancing measures (including avoidance of gatherings, of public places, and of international travel).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is in line with evidence from multi-country studies which suggests that adherence to sensitizing behaviors such as physical distancing has decreased, while adherence to habituating behaviors such as mask wearing has increased (Petherick et al, 2021). Like Chan et al (2021), Petherick et al (2021) also base their results on observational data, but their repeated cross sections are more frequent and span 14 countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations